Corrosion Behavior of Ni3(Si,Ti) in Hydrochloric Acid Solution - Gadang Priyotomo; Yasuyuki Kaneno (International Journal of Science and Engineering, 2013)
The corrosion behaviour of the intermetallic compounds Ni3(Si,Ti) (L12: single phase), has been investigated using an immersion test, electrochemical method, scanning electron microscope in 0.5 kmol/m3 HCl at 303 K. In addition, the corrosion behaviour of austenitic stainless steel type 304 and C276 was studied under the same experimental conditions as references. It was found that the intergranular attack was observed for Ni3(Si,Ti) in the immersion test. From the immersion test and polarization curves, Ni3(Si,Ti) had the moderate corrosion resistance, while the corrosion resistances of C 276 and type 304 were the highest and the lowest. Ni3(Si,Ti) and type 304 were difficult to form a stable passive film, but not for C276. A further experiment must be conducted to clarify the stability of film for Ni3(Si,Ti) in detail.